'Diabetes doesn't matter as long as we're keeping traditions alive': a qualitative study exploring the knowledge and awareness of Type 2 diabetes and related risk factors amongst the young Punjabi Sikh population in the UK. Issue 4 (19th May 2022) - Sidhu, Tarnjit; Lemetyinen, Henna; Edge, Dawn
ABSTRACT: Objectives: It is well known that Sikhs are at an increased risk of Type 2 Diabetes (T2DM) due to a genetic predisposition. High level of education is associated with lower incidence of T2DM. Young Sikhs are well educated compared to other South Asian sub-groups. Despite this, T2DM rates remain high in Sikhs. The uptake of preventative services is also low within Sikhs. At present, no research has been conducted with the young Punjabi Sikh population on diabetes awareness in the UK. To address this gap, this study explores the knowledge and awareness of T2DM and related modifiable risk factors in the UK Punjabi Sikh community. Views surrounding T2DM health-seeking behaviours are also explored. Design: A qualitative design comprising of 1-to-1 semi-structured interviews was adopted. Thirteen Punjabi Sikh participants between the ages of 18–30 took part. Participants were recruited through a Sikh temple and University of Manchester Sikh Society using purposive and snowball sampling in West Yorkshire and North West England. Data were analysed using inductive thematic analysis taking a critical realist stance. Results: Three themes were identified: (1) Perceptions of the causes of T2DM, (2) Perceptions of factors impacting physical activity and diet, and (3) Attitudes towards health-seeking behaviours. Conclusions: The findings show that although well educated, participants overlooked physical activity as contributing factor towards T2DM onset. Additionally, gender and cultural norms influenced physical activity and diet, as these are passed through generations to preserve the collectivist Sikh culture. Exploration of health seeking behaviours also found young Punjabi Sikhs perceived the internet to be the preferred tool to seek T2DM information. These findings hold implications for health professionals, as the information and preventative services provided to Sikhs can be tailored to be culturally appropriate and in line with cultural and gender norms, such as bhangra dancing for physical activity.